Simultaneous Estimation of Ketorolactromethamine and Tiemonium methylsulphate in biofluids by a New Validated UPLC Method - Mohammad Nasir Uddin; Monir Uddin; Md. Touhidul Kabir (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
An UPLC method has been developed for the simultaneous determination of ketorolac Tromethamine and tiemonium methylsulphate in pharmaceutical and biosamples. Calibration curves were linear with correlation coefficient 0.9997 over a studied concentration range of (01-10μg m ) for both drugs. Method was found to be reproducible with relative standard deviation (RSD) for intra to be 0.32-0.99% for KTR and 0.40-1.01% for TMS and inter day precision to be 0.51-2.77% for KTR and 0.41-2.26% for TMS over the said concentration range. The mean recovery of the drug obtained from the intraday assay was 99.18-103.34% for KTR, 99.14-101.76% for TMS and inter-day assay at six different days was 99.39-102.04% for KTR and 98.08-103.78% for TMS. The LOD and LOQ were found to be 0.125 and 0.41μg mL-1, respectively for KTR  and 0.150 and 0.50 μg mL-1, respectively for TMS. Method was successfully validated as per ICH guidelines can be conveniently employed for routine quality control analysis of ketorolac tromithamine and tiemonium methylsulphate in pharmaceutical formulations and biological samples without any interference.